2020
DOI: 10.31925/farmacia.2020.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Potential Influence of Inter- And Intra-Individual Variability of Tacrolimus Exposure on Graft Function Decline in Three-Year Period Following Kidney Transplantation

Abstract: The main goal of the present study was to evaluate the association of tacrolimus (Tac) exposure parameters (trough concentration (TTC), dose-adjusted TTC (C0/D)), Tac intra-individual variability (IPV), and Tac-related gene polymorphisms (CYP3A5 and ABCB1) with kidney function in three-year period after kidney transplantation (Tx). The study enrolled 103 Caucasian patients who were genotyped on CYP3A5 6986A>G and ABCB1 3435C>T polymorphism. High IPV, lower average C0/D, kidney function at 6 months post-transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The present study is the continuation of the research published by Stefanović et al [8], whereby the proposed linear regression model revealed the significant and independent predictors of estimated glomerular filtration rate (eGFR) values up to three years after Tx: established eGFR at 6th month (eGFR6), occurrence of acute rejection episodes within the first-year post-transplantation (AR), Tac IPV, and mean C 0 /D during 6-12 months after Tx.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…The present study is the continuation of the research published by Stefanović et al [8], whereby the proposed linear regression model revealed the significant and independent predictors of estimated glomerular filtration rate (eGFR) values up to three years after Tx: established eGFR at 6th month (eGFR6), occurrence of acute rejection episodes within the first-year post-transplantation (AR), Tac IPV, and mean C 0 /D during 6-12 months after Tx.…”
Section: Introductionsupporting
confidence: 70%
“…After obtaining statistically significant predictors in multivariate regression analysis (Table 3), i.e., eGFR6, Tac IPV, Tac C0/D, sex, and AR, a regression equation was constructed based on the coefficients and causal relationship between the dependent variable and independent predictors, which represents a basis for the MC simulation (Model*). The covariate coefficients in Model* slightly differ from the published model [8] due to different presentations of Tac IPV covariate, but this change was not significant for further analysis. Since the performed regression analysis and MC stimulation included mea values at 6-12 months as predictor and input variable, respectively, an accomp analysis demonstrates a high positive correlation between Tac C0/D at the 3rd (indicative of poor post-transplantation outcomes) and mean C0/D values at 6-12 after Tx (Figure 3).…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations